Irigasi Curah Otomatis Berbasis Sistem Pengendali Mikro - Satyanto Krido Saptomo; Rahmat Isnain; Budi Indra Setiawan (Balai Teknik Irigasi, 2013)
Determination of watering interval and moisture conditioning in sprinkle irrigation requires a supporting technology to optimize the irrigation. Arduino UNO microcontroller was used as an automatic controller that determine in watering based on soil moisture conditions determined by soil moisture sensor. The automatic sprinkle irrigation uses pF parameters to conditioning the soil moisture. Soil potential pF value between 4.2 ≤ pF <2, and are equivalent to the percentage of soil moisture 38.5%≤ soil moisture < 28.7%, were used aslower and upper set point in the automatic irrigation that operates solenoid valve for regulating irrigation water flow from water tank. The result shows that the automatic sprinkle irrigation system could keep the soil moisture between the desired setpoint range and thus can be applied for wider use.